Transformation at Rhodes University: investigating the extent of support for the participation of students with disabilities in the transformation processes of the Institution - Israel, Veronica (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
This study is motivated by the vigorous discourse around transformation at Rhodes University and investigates the extent of support for and engagement with students with disabilities in the transformation processes of the institution. It analyses the extent to which integration is holistic at institutions of Higher Learning. Particular interest is given to the institutional culture of Rhodes University, namely whether it values and embraces diversity and is committed to inclusivity, centering the presence and voice of students with disabilities. It explores institutional responses to students with disabilities and their capacity to flourish beyond notions of access, therefore, delivering on the demand for institutional transformation. The thesis draws on the Critical Disability Studies Approach (CDSA), the social justice reform agenda with reference to the feminist analysis of disability, and the concept of inclusive education. The study uses a qualitative research methodology. The sample size used in the study was sufficient to highlight the challenges students with disabilities at Rhodes University face and their coping mechanisms while investigating the extent of support and active participation in the transformation discourse. The study found that the majority of the participants' academic capabilities were influenced by their disability and impacted on their academic success. The study further revealed that there is a disjuncture between policy and practice in terms of awareness, and as such, effectiveness. While there is a supportive institutional framework, as indicated by more than 50% of the participants in the study, the recommendations ensuing from this research indicate that there are areas in which the university can improve its support mechanisms. Improving support structures is possible through establishing platforms which can be used for students to share their lived experiences and making disability a visible part of the institutional discourse on transformation. The study concludes by arguing for the application of principles of Ubuntu which demonstrate the commitment of Rhodes University in inculcating an inclusive institutional culture and understanding that disability is intersectional with social registers such as race and gender. It emphasises the recognition of the institution as a transforming one if the body that matters is the body whose presence, voice and lived experience is acknowledged and recognised.
Keywords: Rhodes University; Educational change -- South Africa -- Makhanda; Educational equalization -- South Africa -- Makhanda; College students with disabilities -- South Africa -- Makhanda; Students with disabilities -- Services for; Corporate culture -- South Africa -- Makhanda; Critical Disability Studies Approach (CDSA)